2021
DOI: 10.1155/2021/8890725
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and Associated Factors among Under-Five-Age Children in West Guji Zone, Oromia, Ethiopia

Abstract: Background. Stunting is one of the most important public health problems in Ethiopia. It remains a problem of greater magnitude particularly in rural and low-income areas. It reflects chronic nutritional deficiencies and illness that occur during the most critical periods for growth and development in early life. It needs proper intervention to save the future, unless it resulted in diminished cognitive and physical development for the rest of their lives. Therefore, this study aimed to assess the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
15
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
11
15
3
6
Order By: Relevance
“…Similarly, the risk of stunting increased with increasing level of household food insecurity. This finding is similar to studies from Bangladesh (Malay, 2012), Kenya (Benta, 2012) and Ethiopia (Afework et al, 2021). Food insecurity affects the intake of an adequate quantity and quality of diet that, in turn, contributes to childhood stunting.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the risk of stunting increased with increasing level of household food insecurity. This finding is similar to studies from Bangladesh (Malay, 2012), Kenya (Benta, 2012) and Ethiopia (Afework et al, 2021). Food insecurity affects the intake of an adequate quantity and quality of diet that, in turn, contributes to childhood stunting.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, male children were more likely to achieve the minimum acceptable diet than female children. The finding was supported with the study done in Ethiopian adolescents [ 35 ], West Guji Zone, Oromia, Ethiopia [ 36 ] and Sodo zuria District [ 37 ]. This might be due to the culture and or traditional perceptions in Ethiopia mostly give high priority to the male baby than females.…”
Section: Discussionsupporting
confidence: 83%
“…The present study demonstrated that being a boy is associated with stunting (for both employed and unemployed mothers), underweight (employed mothers) and waste (unemployed mothers). This result is different from the one reported from Ethiopia such as Somali Region (48) and West Guji Oromia region (49) , Egypt (50) , Pakistan (51) and South Asia (52) . This could be attributable to male patriotism in some communities where girls are less socially and nutritionally favoured.…”
Section: Discussioncontrasting
confidence: 94%